The Role of Community Health Volunteers in Tuberculosis Prevention Within Surabaya Urban Health Center Service Areas - Laily Hidayati; Armina Latifatul Asna (Universitas Airlangga, 2026)
Introduction: Tuberculosis (TB) remains a critical public health issue requiring the active involvement of community health volunteers (CHVs) for community-level prevention and control. CHVs play strategic roles in health education, case finding, treatment adherence support, and serving as vital bridges between community members and healthcare facilities. This study aimed to explore the roles of CHVs in TB prevention efforts within Surabaya urban health center service areas. Methods: A qualitative study using a phenomenological approach was conducted. Participants comprised 14 TB CHVs recruited via snowball sampling based on predefined inclusion criteria. Data were gathered through in-depth, semi-structured interviews and analyzed using the Miles and Huberman interactive model (data reduction, data display, and conclusion drawing/verification). Results: Six main themes revealed: (1) CHVs' roles in TB prevention (subthemes: health education, screening, treatment supervision, service coordination); (2) CHVs' motivations (intrinsic motivation); (3) CHVs' experiences (positive personal and professional experiences); (4) Challenges faced (psychosocial barriers within the community, administrative bottlenecks, internal personal obstacles); (5) Received support (contributions from family, community, and healthcare professionals); and (6) Future expectations (needs for routine training and improved welfare). Conclusion: CHVs perform vital, meaningful roles in TB prevention that are driven by intrinsic motivation, positive experiences, and multi-source support. However, they continue to face significant structural and psychosocial challenges. Strengthening support systems through continuous training, streamlined administrative processes, enhanced policy backing, and improved CHV welfare is essential to maximize the effectiveness and sustainability of TB control programs. Keywords: Tuberculosis, Community Health Volunteers, Public Health Center, Role Evaluation